STUDI KASUS SIKAP DAN PENGETAHUAN IBU HAMIL DENGAN KEJADIAN ANEMIA BERAT TERHADAP PENGGUNAAN KONSUMSI TABLET FE DI PUSKESMAS WILAYAH BANJARMASIN: STUDI KASUS SIKAP DAN PENGETAHUAN IBU HAMIL DENGAN KEJADIAN ANEMIA BERAT TERHADAP PENGGUNAAN KONSUMSI TABLET FE DI PUSKESMAS WILAYAH BANJARMASIN - Syahrida Wahyu Utami; Nur Cahyani Lestari (Universitas Batam, 2024)
ABSTRACT Background: Anemia in pregnancy is a condition of pregnancy with hemoglobin levels below 11gr% in the 1st and 3rd trimester or levels <10.5gr% in the 2nd trimester. Blood will increase in excess during pregnancy, which is commonly called hydremia or hypervolemia. At the Sei Mesa Community Health Center, Banjarmasin, from January to May there were 32 pregnant women who experienced anemia and this was in the second and third trimesters of pregnancy. Objective: The aim of this research is to determine the description of the knowledge and attitudes of pregnant women who experience anemia towards consuming FE tablets at the Sei Mesa Community Health Center, Banjarmasin. Method: The research was conducted at the Sei Mesa Community Health Center, Banjarmasin, with the research method used being the observation method. The population was 39 people with a sample of 32 people, the sampling technique was porpusive sampling where all members of the population were used as samples. Results: The results of research at the Sei Mesa Community Health Center, Banjarmasin, were that respondents who had good knowledge were 8 people or 25%, 18 people or 56.25% were sufficient, while less than 6 people or 18.75%, and respondents who had a supportive or positive attitude towards consumption of Fe tablets was 26 people or 81.25% and negative attitudes towards it were 6 people or 18.75%. Conclusion: Based on the research, it was concluded that the knowledge of pregnant women who experienced severe anemia at the Banjarmasin Regional Health Center regarding the use of Fe Tablet Consumption was in the poor category and had a negative attitude. Keywords: Knowledge, Attitude, Consumption of Fe Tablets, Anemia